2019
DOI: 10.1111/cob.12327
|View full text |Cite
|
Sign up to set email alerts
|

Total and regional body fat status among children and young people with cerebral palsy: A scoping review

Abstract: Summary The purpose of our scoping review was to determine if children and young people with cerebral palsy (CP) have elevated total or regional body fat compared to children and young people without CP. Databases (Ovid MEDLINE, Embase Ovid, CINHAL and Scopus) were systematically searched from 1 January 1993 to 7 December 2018 in order to identify articles that compared weight status, total body fat or regional body fat (eg, abdominal) between children and young people (0‐21 years) with and without CP. Extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 66 publications
(300 reference statements)
1
14
0
Order By: Relevance
“…Furthermore, because of their growth retardation it is difficult to apply the available centile grids enabling assessment of weight and growth rates, and commonly used in evaluating nutritional status of normally developing children [14]. Moreover, the interpretation of body fat using % fat is also affected by low fat-free mass given the interdependency of fat and fat-free mass to estimate % fat [15]. In view of these significant limitations linked with other measurement methods, bioelectrical impedance analysis (BIA) is more and more commonly applied in assessing nutritional status recognised by clinicians monitoring nutritional status of children with CP [12,13].García Íñiguez et al showed that there is a direct correlation between resting energy expenditure, total energy expenditure and fat mass, muscle mass, and total body water in children with CP [16].…”
mentioning
confidence: 99%
“…Furthermore, because of their growth retardation it is difficult to apply the available centile grids enabling assessment of weight and growth rates, and commonly used in evaluating nutritional status of normally developing children [14]. Moreover, the interpretation of body fat using % fat is also affected by low fat-free mass given the interdependency of fat and fat-free mass to estimate % fat [15]. In view of these significant limitations linked with other measurement methods, bioelectrical impedance analysis (BIA) is more and more commonly applied in assessing nutritional status recognised by clinicians monitoring nutritional status of children with CP [12,13].García Íñiguez et al showed that there is a direct correlation between resting energy expenditure, total energy expenditure and fat mass, muscle mass, and total body water in children with CP [16].…”
mentioning
confidence: 99%
“…Skinfold thickness is well correlated with total body fat in a general paediatric population and also considered appropriate as a single measurement 52,53 . It may not be as accurate in children with CP with more central fat deposits, which is not reflected in reduced peripheral skinfolds 5,50 . Measures of body composition are preferred because of their accuracy and ability to account for compromised growth and altered body composition 29,37 .…”
Section: Discussionmentioning
confidence: 99%
“…52,53 It may not be as accurate in children with CP with more central fat deposits, which is not reflected in reduced peripheral skinfolds. 5,50 Measures of body composition are preferred because of their accuracy and ability to account for compromised growth and altered body composition. 29,37 Further, some studies showed that methods like skinfold and BIA are able to detect both over-and undernutrition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a non-CP cohort with significant muscle deficits, cystatin c-based eGFR was a better predictor of kidney function than creatinine-based eGFR (34). Although since cystatin c is expressed by adipose tissue (35), more work is needed to identify whether cystatin c or creatinine may be a better biomarker to estimate kidney function in populations with low muscle and high body and regional fat stores, such as CP (3,5,36,37).…”
Section: Discussionmentioning
confidence: 99%